Pengaruh Variasi Konsentrasi Propilen Glikol Sebagai Enhancer Terhadap Sediaan Transdermal Patch Ibuprofen In Vitro - Misnamayanti, Misnamayanti; Sugihantoro, Hajar; Fauziyah, Begum (Journal of Islamic Pharmacy, 2019)
Ibuprofen is an anti-inflammatory class of non-steroidal propionic acid used in the treatment of osteoarthritis, analgesics, and antipyretics. Ibuprofen made in a transdermal patch to avoid side effects of irritation to the stomach, first pass effect on application oral. This aims of the research to determine the physical characteristics of the patch, the effect of propylene glycol concentration (150 mg, 200 mg, 250 mg) on the thickness patch, pH, and the rate of penetration as increase in penetration of the ibuprofen transdermal patch. Patch preparations were made in 3 draft formulas with varying concentrations of propylene glycol 150 mg, 200 mg, and 250 mg. The method used for penetration testing is Franz diffusion cells. The results of physical characteristics are clear, odorless, dry, not cracked, 300 folds, thickness ranges from 0.142 to 0.184. The concentration of propylene glycol effects (p-value 0.05) the penetration and no effect (p-value 0.05) the pH test. Increasing the concentration of propylene glycol causes an increase medicine that penetrate the skin.Keywords: Ibuprofen, transdermal patch, propylene glycol